Implementation of Integrated Risk Management in Planning and Budget Governance - Hardino; Indasah; Katmini (Journal Of Nursing Practice, 2025)
Background: Hospitals that implement patient safety principles are obliged to identify and control all important strategic and operational risks. Purpose: This research was conducted to explore the application of integrated risk management in planning and budget management at Sultan Imanuddin Pangkalan Bun Hospital. Methods: The design of this research is qualitative research with a phenomenological approach with the focus of the research directed at exploring the application of integrated risk management in planning and budget management at Sultan Imanuddin Pangkalan Bun Hospital. Apart from that, with a qualitative approach. The informants in this research were the owners or people in charge of the clinic, a total of 5 (Five) people with triangulation of sources. Results: To identify planning and budget governance at Sultan Imanuddin Pangkalan Bun Regional Hospital, the steps involve identifying existing governance at the hospital. This helps management in improving process effectiveness, reducing financial risks, and improving the quality of healthcare services. Even though risk analysis has been implemented well, there are still several aspects that need to be improved. Risk evaluation at Sultan Imanuddin Pangkalan Bun Hospital refers to the ISO 31000:2018 standard or guidelines from the National Patient Safety Committee. Conclusion: Identification and evaluation of planning and budget management at Sultan Imanuddin Hospital, Pangkalan Bun, is important for improving processes, reducing financial risks, and increasing the quality of health services.